Interface entre políticas públicas de saúde mental e economia solidária: a inserção socioprodutiva de pessoas com transtornos mentais - CANCELA, Ana Giselle Ribeiro (Universidade Federal do Pará, 2013)
The work and madness interface has been constructed and reconstructed along the history, therefore, using the work is not a novelty in the field of mental health, it is related to the birth of psychiatry, in a context of transformation of production relation, with a justification and purpose of social control, exploitation of labor and moral treatment. However, from the Psychiatric Reform Process the job enters the scene from new perspectives. Accordingly, this study analyzes the relationship between the mental health policies where work is associated with the solidarity economy, in order to understand the meaning attributed to the associated work, seeking to identify their social productive insert practices and how that is incorporated into the Field of mental health in the State of Pará. this is a qualitative research, based on interviews, observations in locos, survey of documentary and institutional material. at the same time, was realizaed the study using the material, so that the data were organized, and highlight the experiences observed by means of workshops and / or production developed in replacement services, as well associations and cooperatives. Was Obtained in the result that the social and productive activities related to mental health services are part of the CAPS developed, but are also encouraged from these spaces as in the case of the Brightness and Light, the only association of people with mental disorders. Despite, if they show incipient and fragile in its constitution, requiring adequate infrastructure and resources, therefore, no possibility of autonomy and independence from their partners, especially government, it is found in the individual strengths of people entered. It is to note that recent experiments in Brazil, especially in state of Para public policies targeted mental health interface with the social economy, and constitute an ongoing process.